STRATEGY FOR IMPLEMENTING FISH QUARANTINE POLICY IN NORTH SUMATRA IN THE CONTEXT OF PREVENTING THE ENTRY OF QUARANTINE FISH PESTS AND DISEASES BASED ON LAW NUMBER 21 OF 2019 - Muhammad Arif Suparman; Tamaulina Br. Sembiring (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Quarantine practices in Indonesia have evolved since the Dutch East Indies era and have undergone significant transformations, particularly with the enactment of Law No. 21 of 2019. This law integrates the quarantine of animals, fish, and plants, and aligns regulations with contemporary issues. However, its implementation faces challenges, especially in preventing the entry of Quarantine Fish Pests and Diseases (QFPD), such as the case of Koi Herpes Virus in Lake Toba. This study aims to analyze strategies to prevent the entry of QFPD in North Sumatra. The research employs a normative legal method with a prescriptive and statutory approach. Data were collected through literature review and analyzed descriptively and qualitatively. The findings of the study identify and analyze several strategies for preventing the entry of QFPD in North Sumatra, including: institutional integration of quarantine under the Indonesian Quarantine Agency (Barantin), utilization of digital systems and Big Data, a layered quarantine inspection approach (pre-border, at-border, and post-border), risk-based surveillance and inspection, strengthening diagnostic laboratory capacity through modern technology and inter-laboratory networks, stakeholder education and capacity building, enhancement of national and international cooperation, periodic monitoring and reporting for early detection, and strict law enforcement to ensure compliance with quarantine regulations.